A Cyber - based DSS for a Low Carbon Integrated Waste Management System in a Smart City. Issue 3 (2015) - Digiesi, S.; Facchini, F.; Mossa, G.; Mummolo, G.; Verriello, R.
Abstract: Sustainable Integrated Waste Management System (IWMS) is one of the big challenges of modern society. The topic is nowadays a priority since it contributes to the goals set by "EU 2020 Strategy". New web-based technologies are now available to monitor, manage and elaborate information concerning spatially decentralized systems interacting each other by cloud computing. A growing interest is paid to potential applications of these technologies to manufacturing systems and to municipal services ensuring both flexibility and efficiency. The authors propose a Decision Support Systems (DSS) for a Social - Cyber - Physical framework suitable for the strategic planning and operational phases, by supporting public administrators at municipal level in design and plan an IWMS. The main goal of the DSS is minimize the net carbon emissions of the IWMS. The model has been applied to a middle size city located in Southern Italy. A comparative analysis is carried out investigating the optimization of the stand-alone collecting phase and of the overall IWMS. Results in both cases suggest the adoption of multi stream grouping systems for dry recycled fraction and of single stream grouping system for organic and glass fraction. At the same time a different mix of waste collection modalities is found in the two reference cases.